2022
DOI: 10.1038/s41467-022-32411-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom nanozymes catalytically surpassing naturally occurring enzymes as sustained stitching for brain trauma

Abstract: Regenerable nanozymes with high catalytic stability and sustainability are promising substitutes for naturally-occurring enzymes but are limited by insufficient and non-selective catalytic activities. Herein, we developed single-atom nanozymes of RhN4, VN4, and Fe-Cu-N6 with catalytic activities surpassing natural enzymes. Notably, Rh/VN4 preferably forms an Rh/V-O-N4 active center to decrease reaction energy barriers and mediates a “two-sided oxygen-linked” reaction path, showing 4 and 5-fold higher affinitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 73 publications
2
80
0
1
Order By: Relevance
“…The significance of the M-O species is not limited to nonnoble metal SAzyme reactions. In another elegant study, the M-O active species was also proven to be responsible for the high catalytic efficiency of Rh-N 4 and V-N 4 SAzymes [50]. The stable attachment of the O atom lowers the ionization of the metallic atom, resulting in more effective decomposition of the H 2 O 2 molecule.…”
Section: Overview Of Nanozymes' Catalytic Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…The significance of the M-O species is not limited to nonnoble metal SAzyme reactions. In another elegant study, the M-O active species was also proven to be responsible for the high catalytic efficiency of Rh-N 4 and V-N 4 SAzymes [50]. The stable attachment of the O atom lowers the ionization of the metallic atom, resulting in more effective decomposition of the H 2 O 2 molecule.…”
Section: Overview Of Nanozymes' Catalytic Mechanismmentioning
confidence: 98%
“…By further combining Fe-N 4 active sites as the prosthetic group and Fe clusters as cofactors, multiple enzyme-like activities are comparable to natural peroxisome [49]. Expanded Rh-N 4 showed a 20-fold improved affinity compared to natural catalase by imitating the atomic coordination structures of active sites [50]. The specificity of nanozymes can be achieved by introducing enzyme-like binding pockets.…”
Section: Biomimetic Structural Design In Molecularscalementioning
confidence: 99%
“…In recent years, singleatom nanozymes with well-defined electronic and geometric structures have attracted extensive attention. 6,[14][15][16][17][18][19][20][21] The single-atom nanozymes can be regarded as a class of analogs of natural enzymes with catalytic centers at the atomic level. 16,18,[22][23][24][25][26][27][28][29][30] For example, the single Fe atom nanozyme Fe-N-C possesses a unique Fe-Nx active moiety, similar to the heme cofactor in CYP [31][32][33][34][35][36] and highly biomimetic iron oxo intermediates in substrate oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Meanwhile, the light-driven rapid electron transfer and the accumulation of light-triggered reactive oxygen species (ROS) by nanozymes favor the acceleration of the oxidation of enzymatic substrates, resulting in enhanced enzyme-mimetic performance. 14,25 In this contribution, inspired by the studies above, we combined the optical properties and intrinsic enzyme-like performance of CuMnO 2 NFs to realize light-tailored enzyme activity. CuMnO 2 NFs are reported to exert intrinsic peroxidase-and oxidase-like activities.…”
mentioning
confidence: 99%
“…To the best of our knowledge, one of the major challenges and the high-profile question of the current approach for nanozymes is designing superior catalytic activity over naturally occurring enzymes. So far, it has been demonstrated that nanozymes’ catalytic activity can be tailored via constructing atomic structures, surface modification, size-morphology modulation, external trigger employment, etc. In fact, applying external triggers, especially external light irradiation, to tune the enzyme-like reaction may be highly desirable to optimize the catalytic activity of nanozymes because it offers high spatiotemporal resolution without the involvement of physical contact. , Meanwhile, the light-driven rapid electron transfer and the accumulation of light-triggered reactive oxygen species (ROS) by nanozymes favor the acceleration of the oxidation of enzymatic substrates, resulting in enhanced enzyme-mimetic performance. , …”
mentioning
confidence: 99%